Peningkatan kemampuan siswa mengolah rumus pada materi pesawat sederhana melalui model make a match - Hartati, Sri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This Classroom Action Research is the application of the make a match (group-based) learning model applied in the classroom based on the students' difficulties in simple aircraft material. The purpose of this learning improvement action is to improve students' ability to process formulas on simple machine material for class VIII.1 students with Competency Competency Standards (SK) Understanding the role of effort, style, and energy in everyday life. The results, the implementation of cycle 1 in the classroom shows that by applying/using. The group-based learning model obtained an average score of 69.59 students. In cycle 2 the average score of students rose to 76.89. With the group-based scientific learning model, it turns out that it can improve students' abilities in simple aircraft material. These competencies can be seen from the first indicator, students are happy and active in learning activities. Second, the increasing ability of students in simple planes. Thus in the learning process students are able to build their own concepts about learning materials from the results of group learning activities, not the results of the presentation from the teacher. The teacher's role is only as a guide. This learning model is recommended to MTsN teachers as an alternative to improve students' abilities in simple machine process materials. So it can be concluded that from the implementation of the activities in cycle 1 and cycle 2, there was an increase in the grades of VIII.1 MTsN Bonjol students on the simple plane material.